2008
DOI: 10.1007/s00467-008-0785-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease after liver, cardiac, lung, heart–lung, and hematopoietic stem cell transplant

Abstract: Patient survival after cardiac, liver, and hematopoietic stem cell transplant (HSCT) is improving; however, this survival is limited by substantial pretransplant and treatmentrelated toxicities. A major cause of morbidity and mortality after transplant is chronic kidney disease (CKD). Although the majority of CKD after transplant is attributed to the use of calcineurin inhibitors, various other conditions such as thrombotic microangiopathy, nephrotic syndrome, and focal segmental glomerulosclerosis have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 90 publications
0
27
0
3
Order By: Relevance
“…Renal dysfunction, proteinuria, and hypertension may also be observed in transplant recipients who do not develop TA-TMA [26]. Alternative etiologies, other than TA-TMA, in this patient population include, but are not limited to, exposure to nephrotoxic and prohypertensive medications and infections such as BK virus nephropathy [27,28].…”
Section: Clinical and Histologic Featuresmentioning
confidence: 99%
“…Renal dysfunction, proteinuria, and hypertension may also be observed in transplant recipients who do not develop TA-TMA [26]. Alternative etiologies, other than TA-TMA, in this patient population include, but are not limited to, exposure to nephrotoxic and prohypertensive medications and infections such as BK virus nephropathy [27,28].…”
Section: Clinical and Histologic Featuresmentioning
confidence: 99%
“…Particular risks factors for HSCT‐related CKD are seldom delved into or followed over long‐term periods. However, several smaller retrospective studies have demonstrated the overall related risks of CKD in pediatric patients . There is a statistically significant association of CKD at 1 year post‐transplant in HSCT patients who developed or maintained AKI at 3 months post‐transplant .…”
Section: Ckd In Hsctmentioning
confidence: 99%
“…Chronic kidney disease in long-term survivors after HCT occurs with a reported prevalence from 4% to 89% 50,[82][83][84] depending on the definition used. The National Kidney Foundation Kidney Disease Outcomes Quality Initiative defines chronic kidney disease as a glomerular filtration rate of less than 60 mL/min per 1.73 m 2 for 3 or more months, with or without kidney damage.…”
Section: Long-term Renal Complicationsmentioning
confidence: 99%